Mapping personalization policies into software structures - Rossi, Gustavo Héctor; Fortier, Andrés; Cappi, Juan M. (2002)
In this paper we analyze the process of personalizing complex ecommerce applications from a software design point of view. We stress that separation of concerns is a key strategy for obtaining high quality and evolvable implementations. In particular, we show that a naive mapping of personalization policies into software rules may result in a bad design compromising the overall software stability. We first explain our perception of e-commerce applications as views on application models, and briefly explain why personalization functionality should be dealt by separating concerns. We next discuss different mechanisms to intercept behavior from the application model to trigger personalization code and finally we compare our approach for combining rules with other object-oriented design structures in contrast to the existing rule models.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 13/03/2009)
Proceedings of the International Workshop on Recommendation and Personalization in E-Commerce, 140-147, May 2002.
Keywords: COMERCIO ELECTRÓNICO; DESARROLLO DE APLICACIONES WEB; APLICACIONES PERSONALIZADAS; PERSONALIZACIÓN